Fires in GunaiKurnai country : landscape fires and their impacts on Aboriginal cultural heritage places and artefacts in Southeastern Australia - Buettel, Jessie (Archaeopress Archaeology, 2023)
Anthropogenic climate change is becoming a reality, and in Australia this means longer wildfire seasons with more intense fires across a wider area. The GunaiKurnai people of southeastern Victoria saw a large proportion of their land decimated by the Gippsland Fires of 'Black Summer' (2019/2020), prompting questions about both the management of country and its heritage resources moving forward and what role traditional ('cultural') burning could play. Bringing together a multi-disciplinary team, this volume investigates these twin issues.